2018
DOI: 10.24083/apjhm.v13i1.33
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Shared Versus Individual Office Space on Therapist Appraisal of Their Work Environment

Abstract: Objective:  The primary objective was to investigate the impact of shared versus individual office space on therapist appraisal of the work physical and social environment, and overall appraisal of working conditions. Method:  Therapists (n = 59) from Child and Adolescent Mental Health Services in Western Australia were surveyed about their appraisal of the social and physical work environment, in addition to their overall appraisal of working conditions. Results:  Compared to therapists with indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
(96 reference statements)
2
3
0
Order By: Relevance
“…According to Danielsson and Bodin (2009), employees working in a traditional office reported greater satisfaction with the ambient conditions and design than employees working in open-plan offices in which noise and the lack of privacy constitute the main cause of work dissatisfaction. Similar conclusions have been found by previous scholars with respect to the effects of open-plan offices on work productivity (McElroy and Morrow, 2010;De Been and Beijer, 2014;Rogers et al, 2018).…”
Section: Main Investigated Outcomessupporting
confidence: 91%
See 2 more Smart Citations
“…According to Danielsson and Bodin (2009), employees working in a traditional office reported greater satisfaction with the ambient conditions and design than employees working in open-plan offices in which noise and the lack of privacy constitute the main cause of work dissatisfaction. Similar conclusions have been found by previous scholars with respect to the effects of open-plan offices on work productivity (McElroy and Morrow, 2010;De Been and Beijer, 2014;Rogers et al, 2018).…”
Section: Main Investigated Outcomessupporting
confidence: 91%
“…In physical work environment literature, studies have generally focused on office design (Oldham and Brass, 1979; Sundstrom et al , 1980; Oldham and Rotchford, 1983; Elsbach and Bechky, 2007). In addition, among the other design characteristics, particular attention has been devoted to lighting/darkness, privacy, noise/distraction (Elsbach and Bechky, 2007), temperature (Sander et al , 2019), aesthetics and artifacts (Pratt and Rafaeli, 2001; Rafaeli and Vilnai-Yavetz, 2004a, 2004b; Vilnai-Yavetz and Rafaeli, 2006).…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to some participants reporting that they felt self-conscious, stressed, and dehumanized from what they deemed to be a judgemental presence (watching, scrutinizing, and verbally commenting on their practices) of their colleagues and administrators. Similar findings in other research on workspaces (Brewer et al, 2017;Kim & de Dear, 2013;Rogers et al, 2018), suggested that having other people in one's workspace affected how they worked (e.g. communal areas were cause for distraction) and felt about their work.…”
Section: People and Relationshipssupporting
confidence: 84%
“…The research revealed that office spaces that were shared or open concept, were more negatively perceived by workers than enclosed spaces (Brewer et al, 2017;Kim & de Dear, 2013;Rogers et al, 2018). Shared and open concept spaces lacked visual and auditory privacy, had higher noise levels, and posed more challenges with regulating temperatures (Kim & de Dear, 2013;Rogers et al, 2018).…”
Section: Research On the Importance Of Workpacementioning
confidence: 99%